A promoção do Psycap nas instituições de ensino superior comunitárias do Rio Grande do Sul e Santa Catarina - Schneck, Aurélia da Luz (Universidade do Vale do Rio dos Sinos, 2017)
This study aimed to research the perception of the professorsabout the Psychological Captal (Psycap) of their cordinator in the degree in Administration in the Private Higher Education from Rio Grande do Sul and Santa Catarina. If the cordinator promotes tHe Psycap in his followers was also analyzed. This study is characterized by being a Field reserch of qualitative and quantitative approach, which was conducted with 157 professors from Rio Grande do Sul and Santa Catarina to which was applied a eletronic survey and it was conducted using 10 Interview of Inventory of Critical Incidents, by way of content analysis technique (RICHARDSON et al., 2008). On quantitative approuch, some variables has influenced the average attributed to Psycap of these coordinators. And at the crossroads of these with the four dimensions of Psycap (self-efficacy, hope, resiliency and optimism), the following resultsemerged: the variable gender did not interfere on the results, i.e. both teachers as teachers attributed homogeneous for the average engineer Psycap. However, variables such as age, quality of relationship, length of service and if the teacher already held the position of Coordinator, presented heterogeneous responses, namely the generational factor influenced on note attributed to the course Coordinator as well as the quality of the relationship where the positive association was observed. As qualitative results, respondents showed, they realize the promotion of Psycap leadershipactions of the Coordinator, especially in the face of political and economic crisis thatthe country faces and in situations of IES evaluation by the Ministry of education and culture (MEC) through the positive performance on the test of the National Examination performance of students (ENADE). However, this still has in its mission a series of bureaucratic and operational activities, impairing performance in strategic management of course coordinates. Another factor that contributes to efficient management is the organizational culture of the IES that directly influence these actions of the leadership of the Coordinator. The results showed that the people and relationship management skills are essential for this play effective leadership Coordinator. These results allow you to flag some opportunities for improvements to the IES implementations, such as: reassessing the role of Coordinator for an innovative University management, the training coordinator to occupy a management position, have greater clarity on the requirements to fill the position of coordinator of travel and promote changes in the organizational culture of the IES, professionalizing them. The validation of the constructs was conducted via factor analysis and reliability estimation of Cronbach's Alpha by the indicator. Professors attributed an average score for the 4 course Coordinator (I kind of agree) and 5 (agree a lot) on a Likert scale of 6 points. That is, the perception of these respondents of the survey they show the Psycapof this coordinator, but none of the dimensions (self-efficacy, Hope, resiliency and Optimism) stood out positively or negatively about others. Similarly, this fact was ratified by examples in the interviews of the Events reported critical incidents.
Keywords: Psycap; Capital psicológico; Coordenador de curso; Docentes; Psychological captal; Course cordinator; Professors; ACCNPQ::Ciências Sociais Aplicadas::Administração